Legendary Route 66 : - Witzel, Michael Karl (Voyageur Press, 2007)
Legendary Route 66, which highlights the sights along America's Main Street with more than 600 photographs of classic gas stations, motels, road signs, postcards, maps, and memorabilia. This unparalleled look at the Mother Road lets you get your kicks on Route 66 through each decade of its existence--from the point auto adventurers first started using this transcontinental route to the days when Okies made it the Dust Bowl road of flight to the 1950s-era tide of vacationers headed west seeking sun. You'll see Route 66 as it was in its heyday and as it is now, the neon glamour of yesterday versus the ghost towns of today.